Assessment of knowledge and healthcare providers’ role in promoting lactation in United Arab Emirates - Gacem, Sabrina Ait; Gacem, Sabrina Ait; Al-Shahwan, Moayad Jamal; Hassan, Nageeb A. G. M.; Hassan, Nageeb A. G. M.; Djessas, Fetta; Djessas, Fetta (International Journal of Research in Medical Sciences, 2017)
Background: This study was performed to assess mothers’ knowledge and awareness level regarding maternal medication intake during lactation and health care providers’ role in promoting lactation. Methods: This study is a cross-sectional, questionnaire based survey study and a convenient sample of (820) breastfeeding mothers in Ajman and Sharjah, United Arab Emirates (U.A.E.) participated in the study. The results were analyzed using the Statistical Package for the Social Sciences (SPSS) version 20. Descriptive statistics were used to summarize the data concerning the demographic characteristics and breastfeeding knowledge. Categorical variables (such as nationality and educational level) were described by using frequency, percentages, bar chart and pie chart. Results: The current study revealed a (72%) of maternal knowledge compared to (60.4%) four years ago and the most identified encouraging factor for the initiation of lactation stated by the respondents was their own decision followed by family support (58.4%, 39.8% respectively). The health care providers’ role was positively improved (58.4%) as observed in the current study compared to (52.1%) four years ago in UAE. Conclusions: An improvement was observed in terms of knowledge among breastfeeding mothers in the UAE compared to previous years as well as healthcare providers’ role which was also positively improved. Pharmacists were observed to have a low impact on the initiation of lactation, but on the other hand it was found that they had a significant role in terms of assessing maternal medication safety during lactation.